The Effect of Socio-Scientific Inquiry Based Learning (SSIBL) Model Assisted by Nearpod on Students’ Problem-Solving Skills on Alternative Energy Material - Pebriyanti, Helmina; Makiyah, Yanti Sofi; Susanti, Ernita; Rahman, Luthfi (Universitas Negeri Surabaya, 2025)
Objective: This study aims to examine the effect of implementing the Socio-Scientific Inquiry Based Learning (SSIBL) model assisted by Nearpod on students’ problem-solving skills. Method: This research employed a quasi-experimental method with a nonequivalent control group design. The study involved experimental and control groups selected through a purposive sampling technique. Both groups were administered a pretest and a posttest. The instruments used in this study included a problem-solving skills test in the form of an essay questions and an observation sheet to assess the implementation of learning. Results: The findings of this research are as follows: (1) There was an increase in the average scores before and after the treatment. (2) The N-gain scores in both classes showed no significant difference (medium category), which was attributed to differences in instructional duration. (2) The implementation of SSIBL learning in both sessions were classified as high, with average percentages of 86.09% and 88.41%. Novelty: This research integrates SSIBL and Nearpod to improve students’ problem-solving skills in alternative energy materials.